2006
DOI: 10.3727/000000006783981882
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Mouse, Rat, and Pig Pancreatic Islet Functions by Coculture with Human Islet-Derived Fibroblasts

Abstract: Development of an efficient preculture system of islets is ideal. Toward that goal, we constructed a human pancreatic islet-derived fibroblast cell line MNNK-1 for a source as a coculture system for freshly isolated islets to maintain islet functions. Human pancreatic islet cells were nucleofected with a plasmid vector pYK-1 expressing simian virus 40 large T antigen gene (SV40T) and hygromycin resistance gene (HygroR). One of the transduced cell lines, MNNK-1, was established and served as a feeder cell in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Fibroblasts can also improve islet cell viability. The essential role of fibroblasts in islet physiological competence has previously been reported, and it was shown that some fibroblast-produced factors can promote islet survival in culture (35,36). In addition, availability of syngeneic or autologous fibroblasts eliminates the risk of immune response against these cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fibroblasts can also improve islet cell viability. The essential role of fibroblasts in islet physiological competence has previously been reported, and it was shown that some fibroblast-produced factors can promote islet survival in culture (35,36). In addition, availability of syngeneic or autologous fibroblasts eliminates the risk of immune response against these cells.…”
Section: Discussionmentioning
confidence: 96%
“…Here, we engineered a three-dimensional composite islet allograft equipped with IDO-expressing fibroblasts and examined whether local expression of IDO, conferred by adenoviral-mediated gene transfer to bystander syngeniec fibroblasts, prevents the rejection of islet allograft. Our approach here is novel compared with other studies that examined the suppressive effect of IDO in islet transplantation (28,29) because 1 ) bystander syngeneic fibroblasts were used as the target of gene transfer instead of islets to avoid deleterious effects of adenovirus infection on islets (3032), 2 ) islets were embedded within an extracellular matrix that by itself improves islet function and viability (33,34), and 3 ) cotransplanted fibroblasts are more than just a source of IDO and can enhance islet physiological competence (35,36). …”
mentioning
confidence: 99%
“…51 Miki et al recently showed that coculture of the mouse, rat, and pig islets with isletderived fibroblasts maintained islet viability, insulin secretion and glucose responsiveness. 52 Cocultured fibroblast would not cause any concern in terms of overproliferation since it was shown that fibroblasts in floating collagen matrices have low levels of DNA synthesis and become quiescent. [53][54][55] Thus, bystander fibroblasts will not have any negative impact on islet viability and function.…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, different strategies were investigated for improving the results of experimental and clinical islet isolation. 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 Among these attempts, the antiapoptotic and protective effects of some compounds, functioning as cytoprotectives, such as nicotinamide, 3 lisofylline, 5 exendine-4, 6 interleukin (IL)4, 10 prolactin 12 and protein kinase C epsilon, 13 were examined on islet cells in vivo and/or in vitro . In other studies, many approaches of cellular application were used.…”
mentioning
confidence: 99%